TiO2‐Oligoaldaramide nanocomposites as efficient core‐shell systems for wood preservation. Issue 23 (18th February 2015) - Oliva, Rosangela; Salvini, Antonella; Di Giulio, Giuseppina; Capozzoli, Laura; Fioravanti, Marco; Giordano, Cristiana; Perito, Brunella
ABSTRACT Homogeneous core‐shell systems were obtained with a growth, in controlled steps, of several oligoamides on TiO2 nanoparticles. Derivatives of natural compounds, such as l‐tartaric acid and α, α′‐trehalose, were used as diesters in the polycondensation reactions with ethylenediamine. TiO2 anatase was chosen because of its high photo‐activity and its antimicrobial activity. The TiO2 nanoparticles had been previously activated then functionalized using two different coupling agents, and finally, the TiO2‐oligoamide nanocomposites were synthesized using two synthetic pathways. The final products were characterized by 1H NMR, 13C NMR, FT‐IR, and transmission electron microscope. These nanocomposites can show improved properties in comparison with the single components (TiO2 nanoparticles or oligoamides), which are useful in many fields, such as antimicrobial coatings for surfaces in cultural heritage conservation. A nanocomposite (TiO2‐polyethylenetartaramide) was used for applicative studies, and it has shown a good efficacy against fungal attack by Trametes versicolor on wood specimens (Fagus sylvatica). © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42047.